2007
DOI: 10.1093/ndt/gfm261
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study of gadodiamide-related nephrogenic systemic fibrosis

Abstract: Increasing cumulative gadodiamide exposure, high-dose epoietin-beta treatment, and higher serum concentrations of ionized calcium and phosphate increase the risk of gadodiamide-related nephrogenic systemic fibrosis in renal failure patients. Severe cases seem to develop primarily among patients in regular haemodialysis therapy at exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(153 citation statements)
references
References 19 publications
7
142
1
3
Order By: Relevance
“…This suggests that the higher phosphate level in ESRD patients may be a risk factor for Gd 3þ release in vivo, as previously suggested by Marckmann et al (46). In normal serum the release of Gd 3þ was about 10 times lower with the ionic linear GBCAs than with the nonionic linear GBCAs (Fig.…”
Section: Role Of Complex Stability: Evaluation Of Marketed Productssupporting
confidence: 79%
“…This suggests that the higher phosphate level in ESRD patients may be a risk factor for Gd 3þ release in vivo, as previously suggested by Marckmann et al (46). In normal serum the release of Gd 3þ was about 10 times lower with the ionic linear GBCAs than with the nonionic linear GBCAs (Fig.…”
Section: Role Of Complex Stability: Evaluation Of Marketed Productssupporting
confidence: 79%
“…Lifetime gadodiamide doses in adult patients with disabling NSF were greater than in patients with nondisabling NSF or in controls. 40 NSF patients had mean 25-day symptom-free periods following gadodiamide administration. [40][41][42] Three months earlier, an Austrian nephrologist reported that five of nine CKD patients who had undergone gadodiamide-enhanced MRIs developed NSF.…”
Section: Nephrogenic Systemic Fibrosismentioning
confidence: 99%
“…40 NSF patients had mean 25-day symptom-free periods following gadodiamide administration. [40][41][42] Three months earlier, an Austrian nephrologist reported that five of nine CKD patients who had undergone gadodiamide-enhanced MRIs developed NSF. 43 In 2008, Marckmann reported that between 2001 and 2006, 18 % of CKD patients at Herlev Hospital with severe renal insufficiency had developed NSF following administration of high-doses of gadodiamide.…”
Section: Nephrogenic Systemic Fibrosismentioning
confidence: 99%
“…NSF tends to affect the middle-aged most often (mean age 46.4 years) (2,23); the oldest reported patient was 87 years old (23)(24)(25). There are currently nine pediatric cases in schoolchildren and adolescents (age 8-19 years), but no reported cases in infants (26).…”
Section: Epidemiologymentioning
confidence: 99%
“…In detail, there is a number of case reports or small case series of patients with NSF who had an acute occlusion of their dialysis access (23,43), required creation of arteriovenous fistula (23,50,51), an angioplasty (50), suffered from deep venous thrombosis (7,44), pulmonary embolism (52), antiphospholipid antibody syndrome (7,27,45,53), protein C deficiency (54,55), renal vein thrombosis of the transplanted kidney (8), an atrial clot (56), peripheral vascular occlusion (43), transient ischemic attacks (43), multiple brain infarcts (43), an episode of atheroembolism (45), graft failure (42,47,48,52,(54)(55)(56), shock (8,50), multiple myeloma (44), lymphoproliferative disorder (48), brain tumor (23), infections (7,48,50), nonspecific inflammation (42), systemic lupus erythematodes (57), hepatic disease (23,45,53), or metabolic acidosis (13,50,54,55). Marckmann et al (25) found in a small case-control study that among CKD patients exposed to Gd-CA those who developed NSF had higher serum calcium and phosphate levels and received higher doses of erythropoietin than those who did not. Grobner (13) found in his very small series of five affected patients that all had metabolic acidosis, while all unaffected patients (n ¼ 4) showed normal findings regarding pH and bicarbonate values.…”
Section: Co-morbiditymentioning
confidence: 99%